Experiential Marketing Strategy To Enhance The Interest Of Visitors Of Liwa Botanical Garden - Indriyani, Susi; Aprilia Hari Purnama (Journal Of Management Analytical and Solution (JoMAS), 2021)
Liwa Botanical garden is an ecotourism objectwhich prioritizes the development of conservation and protection of biodiversity. Liwa Botanical gardens, located in West Lampung Regency, is located on the ridge of the Bukit Barisan Mountains with cool air and beautiful panoramas, so that visitors will be spoiled by beautiful natural scenery. This is a good potential to get visitors who want to enjoy natural beauty tourism. The study aims to determine the effect of experiential marketing strategies on public interest in visiting the Liwa Botanical gardens. This research is a quantitative research by conducting a survey to visitors of Liwa Botanical garden randomly. The results of the study simultaneously use sense, feel, think, act, and relate as variables which aresignificant to people's interest in visiting the Liwa Botanical gardens. The findings of this study are that visitors are strongly influenced by the cool atmosphere of the botanical gardens, and the experience is pleasant and gives an impression during their visit.